Using Word Wall Technique and Vocabulary Mastery on Students’ Writing Skill - Suryadi Suryadi (Pioneer: Journal of Language and Literature, 2022)
The study's purpose was to determine the effect of the word wall approach and vocabulary acquisition on students' writing skills. For this quasi-experimental study, students in MA Negeri 1 Serang's class XI IPA 1 are randomly assigned to one of four different factorial designs, each with a 2x2 nonequivalent control group. Data on learning outcomes were gathered via pre- and post-test activities. The samples consisted of 60 students picked at random and matched to the study's circumstances and objectives. The findings indicate a substantial difference between the experimental and control groups on the posttest. The Fo was 5.225, and the Sig. was 0.025<0.05. Thus, although the null hypothesis was rejected, the research hypothesis was supported. Additionally, it suggests that the impact of combining the word wall approach with vocabulary knowledge on pupils' writing ability varies.